Examining the Effects of Mobile Telephone Communication on the Utilization of Antenatal Care Services Among Expectant Mothers in Kyotera And Rakai Districts, Uganda - Maria, Nakachwa; Frank-Pio, Kiyingi; Miph, Musoke (Journal of Public Health International, 2022)
Uganda still grapples with a high maternal mortality rates of 336 deaths per 100,000. Expectant mothers across the country lack awareness about the availability of antenatal care services; yet attendance of antenatal care services during pregnancy is crucial in protecting the health of women and unborn children. This article describes a protocol for investigating the effectiveness of mobile telephone communication interventions on the utilization of antenatal care services among expectant mothers in the districts of Kyotera and Rakai Districts in Uganda. Under the protocol, 28 health facilities in the districts of Kyotera and Rakai will be selected using simple random sampling and allocated into the intervention and control arms at a ratio of 1:1. A total of 2224 expectant mothers receiving antenatal care from the sampled health facilities will be recruited using systematic sampling. Expectant mothers receiving antenatal care from facilities allocated into the intervention arm will receive mobile telephone voice and text messages reminders for scheduled ANC visits. The mobile telephone messages will further provide maternal health information and availability of ANC services on a fortnightly basis. On the other hand, expectant mothers receiving antenatal care from facilities allocated into the control group will not get any reminders for scheduled ANC visit and maternal health information through the mobile telephone communication platform. Expectant mothers in the control arm will receive standard maternal health care without reminders. Expectant mothers in both groups will provide baseline data, midterm data will be obtained from the ANC registers at 6 moths while end of term data will be collected after an intervention period of 12months. The data collected will include the number of antenatal care visits attended, antenatal care services obtained from the health facilities, sociodemographic factors and mobile telephone usage, ownership and knowledge. The anticipated outcomes are; increased awareness and utilization of ANC services.
Keywords: Mobile Telecommunications; Antenatal Care; Uganda; Utilization; Maternal Mortality.